Predicting common bottlenose dolphin habitat preference to dynamically adapt management measures from a Marine Spatial Planning perspective. (October 2016) - La Manna, G.; Ronchetti, F.; Sarà, G.
Abstract: At the European Level, SACs (Special Areas of Conservation) are considered among the most reliable tools for increasing the efficiency of protective actions and to identify species vulnerability hotspots across spatial scales. Nevertheless, SACs may fail in their scope when design and management are not dynamically adapted to meet ecological principles. Knowledge of the spatial distribution of relevant key species, such as common bottlenose dolphin ( Tursiops truncatus ), is crucial in order to achieve the objective of the Habitat Directive (92/43/EEC), and is a fundamental step in the process of Marine Spatial Planning. From this perspective, new data and analysis are required to produce forecasts at spatio-temporal scales relevant to individual organisms. Here, we propose a study based on a MaxEnt modelling exercise to define the spatial distributional patterns of bottlenose dolphin at different temporal scales (over periods of multiple months and years) to increase the ecological understanding of how the species use the eco-space, and to delimit boundaries of a SAC in the waters surrounding Lampedusa Island, a hotspot for cetaceans in the Southern Mediterranean Sea. We show that bottlenose dolphin prefer shallower feeding grounds that often host complex and rich food webs, but also that this preference is constrained by disturbance factors such as boat traffic. As sea-related tourism, including dolphin-watching, is one of the most important economic activities of the island, the study results can be used from a management perspective, in order to reach a solution regarding two apparently conflicting needs - species protection and economic development. Highlights: MaxEnt was a sufficiently reliable tool in predicting the distribution of Tursiops truncatus. Lampedusa dolphins were tightly associated to the most coastal part of the island. The likelihood of dolphin occurrence in area nearest to the coast reduced in summer. Chlorophyll- a was the second most important predictor of dolphin occurrence. Our findings allow us to suggest a SAC for bottlenose dolphins of about 710 km 2 .